Phase Change Behavior of Sn20Sb80/Si Nano-Composite Multilayer Thin Films. (1st January 2018) - Guo, Xuan; Hu, Yifeng; Chou, Qingqian; Lai, Tianshu; Zhang, Rui; Zhu, Xiaoqin
Abstract : Nano-composite multilayer Sn20 Sb80 /Si thin films were studied by thermal, electrical and optical methods. Compared with Sn20 Sb80, Sn20 Sb80 /Si film was proved to be a more promising candidate for phase change memory device applications because of its higher crystallization temperature (246°C) and larger crystallization activation energy (2.6 eV). The bandgap was broadened with the increase of Si layer thickness. The crystallization of Sn20 Sb80 was restrained after the adding of more Si film layers confirmed by X-ray diffraction patterns. A smoother surface was obtained with the root-mean-square surface roughness of 0.753 nm for [Sn20 Sb80 (3nm)/Si(7nm)]5 thin film. The measurement using the picosecond laser technique showed that [Sn20 Sb80 (3nm)/Si(7nm)]5 thin film could achieve the crystalline-to-amorphous phase transform within 2.8 ns irradiated by the laser pulse.